2018
DOI: 10.1055/s-0043-122493
|View full text |Cite
|
Sign up to set email alerts
|

Complex biliary stones management: cholangioscopy versus papillary large balloon dilation – a randomized controlled trial

Abstract: Background and study aims  Endoscopic removal of biliary stones has high success rates, ranging between 85 % to 95 %. Nevertheless, some stones may be challenging and different endoscopic methods have evolved. Papillary large balloon dilation after sphincterotomy is a widely used technique with success rates ranging from 68 to 90 % for stones larger than 15 mm. Cholangioscopy allows performing lithotripsy under direct biliary visualization, either by laser or electrohydraulic waves, which have similar success … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 38 publications
0
52
0
5
Order By: Relevance
“…Baseline characteristics of the studies are presented in Table . Fourteen studies reported procedure duration . Median duration was 68.7 min, ranging from 30 min to 165 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Baseline characteristics of the studies are presented in Table . Fourteen studies reported procedure duration . Median duration was 68.7 min, ranging from 30 min to 165 min.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the PRISMA flow diagram of selected studies. Of the 24 studies evaluated, 13 were carried out in America, 12,14,15,[17][18][19]21,22,25,26,30,31,35 seven in Asia, 13,20,23,24,27,29,34 three in Europe, 16,28,33 and one was a multinational study spanning America, Asia, and Europe. 32 Ten studies were multicenter.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While SOC appears to be efficacious for the treatment of large bile duct stones, their precise role in the treatment algorithm is unclear. In a randomized controlled trial (RCT) comparing SOC with EHL and endoscopic papillary large‐balloon dilation, 100 patients with difficult bile duct stones were randomized . The main outcome was complete stone removal.…”
Section: Therapeutic Cholangioscopic Proceduresmentioning
confidence: 99%
“…There was no difference in the overall complete stone removal rate, technical success rate, radiologic exposure and adverse events. Procedure time was significantly lower with the use of endoscopic papillary large‐balloon dilation compared to SOC with EHL . In another RCT from our institution comparing D‐SOC with LL and endoscopic papillary large‐balloon dilation, 66 patients were randomized.…”
Section: Therapeutic Cholangioscopic Proceduresmentioning
confidence: 99%